Impact of fresh and aged palm shell biochar on N2O emissions, soil properties, nutrient content and yield of Komatsuna (Brassica rapa var. perviridis) under sandy soil conditions. Issue 2 (3rd March 2020) - Basalirwa, Daniel; Sudo, Shigeto; Wacal, Cosmas; Oo, Aung Zaw; Sasagawa, Daisuke; Yamamoto, Sadahiro; Masunaga, Tsugiyuki; Nishihara, Eiji
ABSTRACT: Biochar can reduce N2 O emissions and it can be added to the soil once, whereas fertilizers are often applied every cultivation season. The aging of biochar in soil affects its functioning but it is unclear whether palm shell biochar (PSB) could still mitigate N2 O emissions even when additional basal N fertilizers are applied 1 year after the initial biochar application. We studied the impact of fresh and aged PSB (0%, 6%, 12%, and 18% w/w of dry soil) on N2 O emissions, soil properties, nutrient content and yield of Komatsuna ( Brassica rapa var. perviridis ) under sandy soil conditions. The aged PSB non-significantly reduced N2 O emissions but significantly offset soil acidification, and maintained a high soil nutrient status. Biochar application with fertilizer significantly increased plant tissue K and Ca content but decreased N, P and Mg content compared to the treatments without biochar. At higher application rates, biochar had negative effects on crop yield but as it aged, the negative effects were offset as a result of the similar variation in plant N uptake. Since seasonal N fertilizer application seems to be inevitable in Komatsuna cultivation, addition of biochar could be a possible way of counteracting the effects of excessive fertilizer use. Further research is needed to assess the feasible biochar application rates for Komatsuna fields in various soil types under field conditions.